2016
DOI: 10.1038/srep31013
|View full text |Cite
|
Sign up to set email alerts
|

Unified Electromagnetic-Electronic Design of Light Trapping Silicon Solar Cells

Abstract: A three-dimensional unified electromagnetic-electronic model is developed in conjunction with a light trapping scheme in order to predict and maximize combined electron-photon harvesting in ultrathin crystalline silicon solar cells. The comparison between a bare and light trapping cell shows significant enhancement in photon absorption and electron collection. The model further demonstrates that in order to achieve high energy conversion efficiency, charge separation must be optimized through control of the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Ray-optics is an approximation that cannot be applied to photonic crystals and accurate modeling of wave-interference based light-trapping in a photonic crystal (PhC) due to multiple coherent scatterings from wavelength-scale micro-structures requires rigorous numerical solution of Maxwell’s equations 1723 throughout the solar cell architecture. A coupled optical-electronic approach and experimental study on a 3 μm -thick cell in 23 showed the possibility of enhanced light-absorption and conversion efficiency in patterned silicon cells as compared to bare silicon cells. However, the light-absorption in this study still falls well below the Lambertian light-trapping limit.…”
Section: Introductionmentioning
confidence: 99%
“…Ray-optics is an approximation that cannot be applied to photonic crystals and accurate modeling of wave-interference based light-trapping in a photonic crystal (PhC) due to multiple coherent scatterings from wavelength-scale micro-structures requires rigorous numerical solution of Maxwell’s equations 1723 throughout the solar cell architecture. A coupled optical-electronic approach and experimental study on a 3 μm -thick cell in 23 showed the possibility of enhanced light-absorption and conversion efficiency in patterned silicon cells as compared to bare silicon cells. However, the light-absorption in this study still falls well below the Lambertian light-trapping limit.…”
Section: Introductionmentioning
confidence: 99%
“…predicts that electrical micro-renewable energy systems such as solar PV could provide 30–40% of the United Kingdom’s electricity needs by 2050 4 . Currently, research in the area of photovoltaics is focused primarily on new technologies such as third generation PV 5 , optimising efficiencies and applications of solar cells by unconventional means 614 .…”
Section: Introductionmentioning
confidence: 99%
“…This equation assumes that every absorbed photon generates a couple of charge carriers contributing to the delivered current. The evaluation of this spectral absorption, , is based on the following equation 53 , 54 : where is the imaginary part of the dielectric permittivity of the material, and is the square of the electric field intensity inside each material. As far as is evaluated at each location of the structure, it is possible to obtain the total absorbed power contributing to the short-circuit current just by integrating within the volume of interest, in this case, the active layer.…”
Section: Methodsmentioning
confidence: 99%